2006
DOI: 10.3168/jds.s0022-0302(06)72298-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Feed and Manure Data Collected on Wisconsin Dairy Farms

Abstract: An on-farm study of 54 representative Wisconsin dairy farms was conducted to evaluate the influence of biophysical and socioeconomic factors on overall feed, fertilizer, and manure nutrient use. This report validates 1) how well data on cow diets, feed analyses, and milk production reflected established feed-milk-manure relationships; and 2) how well farmer-recorded data on manure land application reflected literature values of manure N and P excretion, collection, and loss. Calculated feed N and P use efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 15 publications
3
37
1
1
Order By: Relevance
“…A comprehensive nutrient management survey was conducted on Wisconsin dairy farms during the period -2005(Powell et al 2006. The feed and manure management components of the Wisconsin questionnaire were modified and applied to two dairy farms in Shandong Province, China during June, 2006.…”
Section: On-farm Surveysmentioning
confidence: 99%
See 2 more Smart Citations
“…A comprehensive nutrient management survey was conducted on Wisconsin dairy farms during the period -2005(Powell et al 2006. The feed and manure management components of the Wisconsin questionnaire were modified and applied to two dairy farms in Shandong Province, China during June, 2006.…”
Section: On-farm Surveysmentioning
confidence: 99%
“…• Feed N and P intake were derived from farmerdefined amounts of feed offered to lactating cows (wet basis), multiplied by either direct feed analyses (Wisconsin, Powell et al 2006), literature values of feed DM, N and P concentrations (China, CECAT 1999), or in the case of imported feed concentrates, formulation information provided on feed bags.…”
Section: On-farm Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…Any departure from this assumption should be minimal because variations in average DIM were relatively minor (see Table 2 below). Others have reported that change in body N was likely negligible in estimating N balance of commercial dairy herds (Powell et al, 2006).…”
Section: Sample Analysesmentioning
confidence: 99%
“…As already stated (Grignani and Bassanino, 2000;Mulier et al, 2003;Powell et al, 2006), part of the information supplied by farmers in commercial farming results appears inaccurate, or not known, especially for farm products recycled in animal feeding: further contact with the farmers and their feed consultants was sometimes necessary. When the NP content in some farm products was unknown, it was estimated using standard figures ( for its NP content according to its importance in the animal diet; average data for the chemical composition are reported in Table 2.…”
Section: Data Collectionmentioning
confidence: 99%